Experimental data sets on the evaluation of graphene oxide as a thyroid endocrine disruptor and a modulator of gas gland cells in Japanese medaka (Oryzias latipes) larvae at the onset of maturity - Tolulope E. Asala (Elsevier, 2021)
This article presents the experimental datasets obtained from the histological/histochemical studies of endocrine disrupting effects of graphene oxide (GO) on thyroid follicles and gas gland (GG) cells of Japanese medaka larvae at the onset of maturity. The experiment was conducted on one day-post hatch (dph) starved fries (orange-red variety) immersed in different concentrations of GO (2.5-20.0 mg/L) and no GO (controls) in embryo-rearing medium (ERM) for 96 h under laboratory conditions (25 ± 1 °C; light cycle 16 h light: 8 h dark). After treatment, larvae were maintained in balanced salt solution (BSS) with food and allowed depuration for 6 more weeks in a GO-free environment. On 47 dph, the larvae were anesthetized in MS 222 and their total lengths (mm) and weights (mg) were measured, and they were then cut into three small pieces (head, trunk, and tail). Head and trunk regions were fixed in 4% PFA in 20 mM PBS for 48 h at room temperature and the post-anal tail was preserved in TRI reagent and kept at −20 °C until analysis. Tissues in 4% PFA were used for cutting 5µm thick paraffin sections in a manual rotary microtome. Sections of head regions were evaluated for thyroid follicles after hematoxylin-eosin (HE) or Periodic acid-Schiff (PAS) staining. Trunk sections were used for swim bladder (SB) inflation studies and for phenotypic sex (ovary and testis) of the larvae after HE staining. Genetic sex assessment was made from tail DNA by genotyping Y chromosome-specific male sex-determining gene dmy. Digital images were captured by using either an Olympus B-max 40 microscope attached to a camera with Q-capture Pro 7 software or an Olympus CKX53 microscope with DP22 camera and CellSens software. Images of thyroid follicles and GG cells were analyzed using imagej software. HE stained histological sections of thyroid follicles near the heart and branchial regions were captured and the area (µm2) of individual follicles (minimum 3) available in the entire section were measured. The heights of thyrocytes (µm) were determined directly. Manual counting of GG cells was made from the digital images captured in several regions of the SB avoiding blood cells and other cells which have indistinct nucleus and pale cytoplasm; results were expressed as the number of GG cells/mm2. Data were analyzed by GraphPad prism version 7.04. For normally distributed data, one-way ANOVA followed by post-hoc Tukey's test or unpaired parametric “t” test including Welch's correction was used. Otherwise, Kruskal-Wallis test followed by nonparametric Mann-Whitney's test as a post hoc test was used. Data were expressed as means ±SEM and the level of significance was set at p < 0.05.